Analisis Sentimen Publik Pada Twitter Terhadap Boikot Produk Israel Menggunakan Metode Naïve Bayes - Ade Tiara Susilawati; Nur Anjeni Lestari; Puput Alpria Nina (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The conflict between Israel and Palestine has been a prominent topic of international discourse for several decades. This dispute spans a century, commencing in 1917 and persisting to the present day. This research delves into sentiment analysis of the Indonesian community concerning the Israel-Palestine conflict through the Twitter social media platform, with a specific focus on boycotting Israeli products. Utilizing Orange and Naive Bayes classification, the study analyzes over 300 datasets of tweets acquired through the scraping process. The objective is to comprehend the nuances, trends, and variations in sentiment among Twitter users regarding the issue of boycotting Israeli products. The results reveal that the majority of the population tends to support the boycott, with a Naive Bayes classification accuracy of 95%, Precission of 96%, Recall of 95%, and F1 Score of 95%. The data preprocessing process, encompassing transformation, tokenization, and filtering, effectively eliminates noise and prepares the data for a more in-depth sentiment analysis.